Empowerment of Women Through The Group of Marketers of Pomegranate Fisheries Products Manurung Village In Tanah Bumbu Regency - Dhian Anggraeni; Yusuf Hidayat; Ahmad Yunani; Muhammad Riduansyah Syafari; Andi Tenri Sompa (Wadah Inovasi Indonesia, 2021)
This study found that the first women's empowerment was conducted on groups of processors marketers fishery products (POKLAHSAR) Delima Desa Manurung District of Kusan Middle Tanah Bumbu, an empowerment-based group, named Delima. In the process of empowerment groups, marketers process fishery products Pomegranate empowerment through several stages, including awareness, capacity building, and shuck stage. Both internal factors of the group of marketers processing fishery products Delima, in which the members have the same goal, namely the desire to continue to learn and strive to empower themselves to become the principal capital in the achievement of the empowerment of women in the group. Potential and human resources owned by group members and administrators strongly support the success of women's empowerment in Poklahsar Delima. While external factors support the empowerment of women in Poklahsar Pomegranate, there is a wide range of support, both from the government, the family, the local community, and the natural resources available.